2008
DOI: 10.1002/ccd.21607
|View full text |Cite
|
Sign up to set email alerts
|

Novel bioabsorbable salicylate‐based polymer as a drug‐eluting stent coating

Abstract: This study shows favorable vascular compatibility and efficacy for a novel bioabsorbable salicylate-based polymer as a DES coating, and supports further research and development of this unique class of polymer materials for applications in cardiovascular devices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
36
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(36 citation statements)
references
References 32 publications
(27 reference statements)
0
36
0
Order By: Relevance
“…Most notably, the polymer was associated with reduced inflammation compared with a standard BMS and Cypher stent. 81 This was very likely due to the antiinflammatory properties of salicylic acid following absorption by the vessel wall after its release. Drug elution was found to be complete after 30 days, and complete stent degradation occurred over a 9-to 12-month period.…”
Section: Poly (Anhydride Ester) Salicylic Acid: the Ideal Stentmentioning
confidence: 99%
“…Most notably, the polymer was associated with reduced inflammation compared with a standard BMS and Cypher stent. 81 This was very likely due to the antiinflammatory properties of salicylic acid following absorption by the vessel wall after its release. Drug elution was found to be complete after 30 days, and complete stent degradation occurred over a 9-to 12-month period.…”
Section: Poly (Anhydride Ester) Salicylic Acid: the Ideal Stentmentioning
confidence: 99%
“…Preclinical studies have demonstrated the potential benefit of the anti-inflammatory properties of salicylic acid in combination with an antiproliferative drug. In vitro studies demonstrated a complete stent degradation over 12 months [58,59]. The safety and efficacy of the IDEAL BRS was evaluated in the WHISPER FIM (n = 11).…”
Section: Ideal Bioresorbable Scaffoldmentioning
confidence: 99%
“…Preclinical data are awaited for this iteration. 49 Future of BVS DES is a major breakthrough in interventional cardiology because they reduced the need for repeat intervention compared with BMS by more than 50%. Late (6 month to 1 year) or very late (beyond 1 year) thrombosis is the feared complication of DES that may result in myocardial infarction and death.…”
Section: Biodegradable Magnesium Stentmentioning
confidence: 99%